Investigation of the effects of an intense pulsed ion beam on the surface melting of IN718 superalloy prepared with selective laser melting; Metals; Vol. 10, iss. 9 - Min Min; Ding Shuiting; Yu Xiao; Zhang Shijian; Zhong Haowen; Remnev (Remnyov) G. E. Gennady Efimovich; Le Xiaoyun; Yu Zhou (2020, 2020)
Title screen